Studi Pengaruh Penambahan Lumpur Lapindo Sebagai Bahan Subtitusi Semen terhadap Kuat Tekan Beton - Septian, Rizky Bagus; Hartantyo, Sugeng Dwi; Romadhon, Romadhon (Jurnal Talenta Sipil, 2025)
With the increasing use of concrete in the construction sector, the demand for its constituent materials, particularly cement, has also continued to rise. This study utilizes Lapindo mud as a partial substitute for cement, based on the fact that Lapindo mud contains chemical compounds similar to the main components found in cement. The objective of this research is to determine the effect of using Lapindo mud as a partial cement replacement in concrete. The study was conducted using an experimental method and referred to the Indonesian National Standard (SNI) 03-2834-2000 for concrete mix design. A total of 12 cylindrical specimens were prepared with a target compressive strength of 250 kg/cm² (K-250). The planned Lapindo mud replacement levels were 0% (normal concrete), 2%, 4%, and 6% of the cement content. Compressive strength tests were performed at 28 days of curing using a Compressed Test Machine. The average compressive strengths obtained for concrete mixes with 0%, 2%, 4%, and 6% Lapindo mud were 20.95 MPa, 19.06 MPa, 18.26 MPa, and 17.02 MPa, respectively. Based on the results, it can be concluded that an increase in the percentage of Lapindo mud in the mix leads to a decrease in the compressive strength of concrete.